Geochemistry of sediments from the Cretaceous-Tertiary boundary - Frank T Kyte; Zhiming Zhou; John T Wasson (PANGAEA, 1980)
Siderophilic element concentrations are high in sediments from the Cretaceous-Tertiary boundary. An extraterrestrial source is indicated. Concentrations are too high to be understood in terms of the impact of a chondritic asteroid. Either the projectile was a metal-sulphide core or the infalling material (probably weak cometary matter) was slowed down during atmospheric passage.
Supplement to: Kyte, FT et al. (1980): Siderophile-enriched sediments from the Cretaceous-Tertiary boundary. Nature, 288(5792), 651-656, https://doi.org/10.1038/288651a0